How Will Walking Survive the Driverless Car? (breakout presentation). (December 2017) - Bell, Adrian
Abstract : Background: In 2016, TransLink, the regional transportation authority for metro Vancouver issued a policy report entitled 'The Future of Driving'. The report examined potential options for managing and benefitting from the transformative impacts of new mobility services and automation. In line with TransLink's strategic regional role, the potential for increased vehicle dependence and VKT was highlighted as a risk for transit and active transportation policy. Aim: As traditional models are not able to account for new mobility services, TransLink decided to explore social innovation to inform future policy. The Mobility Innovation Lab, or MI-Lab, creates a safe space for experts, government and industry to gather knowledge on future mobility behaviour, tests ideas and decide how to respond through policy and regulation. Method: TransLink commissioned Activate Planning and EcoPlan International to advise on a suitable model for the MI-Lab. The team researched other social innovation models, developed a concept, interviewed stakeholders and proposed a format. The research will be completed by May 2017 and first Lab sessions are expected by July. Results: By the time of Walk21 the session will have the results of the research and the first meetings. The roundtable format is intended to be a taster of the MI-Lab idea for Walk21 participants and to be part of the lab process that will help shape mobility policy in metro Vancouver towards a safe, shared and active mobility culture. Conclusions: Social innovation is a growing method for dealing with complex modern issues. Transportation once guided by trend-based models, is being disrupted to its core by new technology. New techniques are needed to assess the social impact and policies required of new services and automation, not least of which is the effect on hard-won pro-walking policies. The MI-Lab is intended to bridge this gap and demonstrate opportunity through experimentation. The Walk 21 conference will be one of the first opportunities to hear how this will work.